A Conceptual Exploration of School Accreditation from the Perspective of National Education Policy - Ridho, Muhammad (Yayasan Pendidikan Tanggui Baimbaian, 2026)
This study examines the implementation of school accreditation as a fundamental instrument for quality assurance in basic education in Indonesia through conceptual, legal, and operational analysis. Using library research with a qualitative approach, this study analyzes the concept of accreditation within the quality assurance framework, the legal basis of which includes Law No. 20 of 2003, Government Regulation No. 19 of 2005, and Decree of the Minister of Education, Culture, Research, and Technology No. 246/O/2024, as well as the implementation system which encompasses eight national education standards. According to the study findings, accreditation acts as an external evaluation tool that supplements the Internal Quality Assurance System (SPMI),, but its implementation faces multidimensional challenges including disparities in educational unit capacity, limited assessor competency, and data engineering practices. Strategic recommendations are formulated including strengthening the Total Quality Management approach, revitalizing competency-based assessor training, and optimizing internal quality audits. This research contributes to the development of accreditation policies that can encourage substantive transformation of the quality of basic education in Indonesia.